2022
DOI: 10.2169/internalmedicine.8651-21
|View full text |Cite
|
Sign up to set email alerts
|

New-onset Polymyalgia Rheumatica Following the Administration of the Pfizer-BioNTech COVID-19 Vaccine

Abstract: We herein report the case of an 80-year-old Japanese woman who presented to our hospital with bilateral pain in the shoulders and hips lasting for a month since 2 days after the second dose of the BNT162b2 COVID-19 vaccine. Her physical findings, laboratory data, and ultrasonographic findings of bilateral biceps tenosynovitis and lateral subacromial bursitis were consistent with a diagnosis of polymyalgia rheumatica (PMR). She was successfully treated with oral prednisolone 15 mg/day. Although a causal relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Существенные проблемы в дифференциальной диагностике ИВРЗ в период пандемии COVID-19 возникают у пациентов пожилого возраста. Имеются данные о развитии ревматической полимиалгии (с гигантоклеточным артериитом или без него) и других ИВРЗ на фоне инфекции вирусом SARS-CoV-2 и особенно вакцинации против этой инфекции [46][47][48][49][50][51][52][53]. Это проблема обсуждалась нами на страницах журнала «Научно-практическая ревматология» в самом начале пандемии COVID-19 [54].…”
unclassified
“…Существенные проблемы в дифференциальной диагностике ИВРЗ в период пандемии COVID-19 возникают у пациентов пожилого возраста. Имеются данные о развитии ревматической полимиалгии (с гигантоклеточным артериитом или без него) и других ИВРЗ на фоне инфекции вирусом SARS-CoV-2 и особенно вакцинации против этой инфекции [46][47][48][49][50][51][52][53]. Это проблема обсуждалась нами на страницах журнала «Научно-практическая ревматология» в самом начале пандемии COVID-19 [54].…”
unclassified
“…A handful of cases of PMR following COVID-19 vaccination have been reported [7][8][9], and these patients presented with shoulder pain. Shoulder pain is a typical symptom of PMR and is reported to be found in over 90% of patients; however, some cases of PMR lacking shoulder symptoms have been reported [10].…”
Section: Discussionmentioning
confidence: 99%
“…The second dose of the COVID-19 vaccine was not administered, and an HLA-DRB1 analysis was not performed in either of these patients. Most recently, several studies have reported that PMR and giant cell arteritis (GCA) onset after COVID-19 vaccination is very common ( 12 - 14 ).…”
Section: Discussionmentioning
confidence: 99%